Multiculturalism and identity politics: Reading on the Religious Harmony Forum - Ahmad, Jafar; Wafi, Mahmud Hibatul; Mushkalamzai, Ziaulrahman; Hadi, Al Amin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
This study looks into identity politics locally, with an emphasis on the role played by religious groups—such as the Religious Harmony Forum (Forum Kerukunan Umat Beragaman/FKUB)—in promoting multiculturalism as a countermeasure to the growth of identity politics. The study’s focus is the Kerinci Regency in Jambi, Indonesia, and it looks at how identity politics and diversity are positioned within the larger Indonesian framework. The research selectively chooses informants, such as the FKUB, the Election Supervisory Agency (Bawaslu), traditional leaders, and religious figures, using qualitative methods like observation, interviews, and document examination. Results show that a variety of political identification patterns exist across the country according to societal culture, resources, and sociopolitical circumstances. As a result, the FKUB responds with a variety of strategies and tactics. The study also emphasizes how the discourse-centric perspective on multiculturalism hinders its ability to effectively counter identity politics. The research points up difficulties that stand in the way of achieving diversity, such as the consolidation and contestation of identity within Islam. Interfaith conflicts, however, show a downward trend and provide a more nuanced picture of the intricate relationship between identity politics and multiculturalism in Indonesia at the local level.